Adenomatoid odontogenic tumor. Case report - Deza Palle, Jonathan (2018)
The adenomatoid odontogenic tumor (AOT) is a benign epithelial odontogenic tumor that occurs in young female patients with a higher incidence in the maxillary region. The AOT is slow-growing, progressive, minimally invasive and asymptomatic tumor, that is related to un erupted tooth organs. The choice treatment is enucleation and curettage of the affected area with a rare recurrence. This case report describes an 8-year-old patient with a AOT located in the maxillary region on the right side; the symptomatology, the imaging evaluation and the proposed surgical treatment are described. The evolution was favorable; there was no tumor recurrence.